High-pressure EXAFS Debye-Waller factors of metals - Tuyen, Nguyen Viet; Hai, Tran Thi; Hong, Nguyen Thi; Hong, Phan Thi Thanh; Hieu, Ho Khac (VNU Journal of Science: Mathematics - Physics; Vol 33 No 1, 2017)
Abstract. The anharmonic correlated Debye model has been developed to investigate the pressure effects on the extended X-ray absorption fine structure (EXAFS) Debye-Waller factors of metals. The recent well-established Grüneisen parameter expressions have been applied to formulate the pressure-dependent analytical expressions of the effective spring constant, correlated Debye frequency and temperature. Combing with the anharmonic correlated Debye model, the expression of EXAFS Debye–Waller factor under pressure can be derived. Numerical calculations, performed for Fe and Cu metals show reasonable agreement with experiments.